Lightweight Deep Learning Models for Lung Disease Classification Using Chest X-ray Images - Abdullah Sholum; Aji Prasetya Wibawa; Ardhana Putra Agustavada; Dafa Fadhilah Hilmi; Felix Andika Dwiyanto (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2026)
Lung disease classification from chest X-ray images using deep learning has attracted significant attention due to its potential to support rapid and automated medical diagnosis. However, many deep learning models require high computational resources, limiting their applicability in resource-constrained environments. This study evaluates the effectiveness of lightweight deep learning architectures for lung disease classification using chest X-ray images consisting of COVID-19, Normal, and Pneumonia classes. Three architectures were comparatively analyzed, including a baseline Convolutional Neural Network (CNN), EfficientNetV2, and MobileNetV2. All models were trained and evaluated under identical preprocessing and experimental conditions using a dataset of 697 chest X-ray images with a 60:20:20 split ratio for training, validation, and testing. Experimental results show that EfficientNetV2 and MobileNetV2 achieved classification accuracy up to 0.99 with AUC-ROC values approaching 1.0. In terms of computational efficiency, both lightweight architectures reduced trainable parameters by approximately 99.3% compared to the baseline CNN, decreasing from 576,851 to 3,843 trainable parameters through transfer learning with frozen pretrained layers. MobileNetV2 achieved this performance with 0.613 GFLOPs and a model size of 9,435 KB, while EfficientNetV2 required 0.781 GFLOPs and 15,993 KB. Although EfficientNetV2 demonstrated slightly more stable performance, MobileNetV2 provided the most effective trade-off between classification accuracy and computational efficiency, making it more suitable for deployment in resource-constrained healthcare environments. These findings demonstrate the feasibility of lightweight deep learning architectures for efficient and reliable lung disease classification from chest X-ray images